(untitled) (Global Journal of Science Frontier Research, 2023)
The authors discuss the contradictions between the main sections of the modern physical picture of the universe In the Unitary Quantum Theory UQT it was shown that space and time become Newtonian again 4 and the growth of the particle mass with increasing speed comes from other considerations of physics 1 page 6 Unlike quantum theory the modern theory of gravity general relativity has not been confirmed by experiments and needs a significant revision The authors propose a new approach to the kinetic theory of gravity which is a natural extension of the UQT